2019
DOI: 10.1158/1078-0432.ccr-18-2967
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Diffusion-weighted Imaging to Decrease Unnecessary Biopsies Prompted by Breast MRI: A Trial of the ECOG-ACRIN Cancer Research Group (A6702)

Abstract: Purpose: Conventional breast MRI is highly sensitive for cancer detection but prompts some false-positives. We performed a prospective, multicenter study to determine whether apparent diffusion coefficients (ADCs) from diffusion weighted imaging (DWI) can decrease MRI false-positives. Experimental Design: 107 women with MRI-detected BI-RADS 3, 4, or 5 lesions were enrolled from March 2014 to April 2015. ADCs were measured both centrally and at participating sites. Receiver operating characteristic (ROC) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 40 publications
7
93
0
6
Order By: Relevance
“…The ROI should be drawn completely within the lesion, consistent with the hyperintense areas on high b value DW MRI, while avoiding normal tissue and areas of necrosis, hemorrhage, or fat by cross referencing with the contrastenhanced T1-weighted images or unenhanced T1-and T2-weighted images, if available (12, 43). On the subject of the size of the ROI to be used, two multicenter trials in the United States employed the method of drawing the ROI for the entire lesion and measuring the average ADC across a lesion (44,45). However, according to a recently published international expert agreement, the use of a small ROI placed on the darkest part of the lesion on the ADC map that represents the most suspicious area is suggested as the preferred method for measuring ADC values, in order to reduce the inter-and intra-reader variability and improve the diagnostic performance of breast DW MRI (13).…”
Section: Quantitative Assessment On Dw Mrimentioning
confidence: 99%
“…The ROI should be drawn completely within the lesion, consistent with the hyperintense areas on high b value DW MRI, while avoiding normal tissue and areas of necrosis, hemorrhage, or fat by cross referencing with the contrastenhanced T1-weighted images or unenhanced T1-and T2-weighted images, if available (12, 43). On the subject of the size of the ROI to be used, two multicenter trials in the United States employed the method of drawing the ROI for the entire lesion and measuring the average ADC across a lesion (44,45). However, according to a recently published international expert agreement, the use of a small ROI placed on the darkest part of the lesion on the ADC map that represents the most suspicious area is suggested as the preferred method for measuring ADC values, in order to reduce the inter-and intra-reader variability and improve the diagnostic performance of breast DW MRI (13).…”
Section: Quantitative Assessment On Dw Mrimentioning
confidence: 99%
“…X-ray mammography screening is characterized by a high level of sensitivity in detecting abnormal breast masses, but relatively low specificity in assessing malignancies 1 . This has triggered an increasing interest in additional methods for clarifying ambiguous findings, especially using magnetic resonance imaging (MRI) to avoid the large number of unnecessary biopsies [2][3][4][5][6][7] . A recent and successful trend has been the use of abbreviated, contrastagent free protocols based on diffusion-weighted imaging (DWI) and T2-weighted acquisitions, especially in the light of the required short examination times and the possible side effects of Gadolinium containing contrast agents 8 , which is especially relevant when aiming to apply these techniques during the clarification process of routine screening 3,[9][10][11] .…”
Section: Influence Of Residual Fat Signal On Diffusion Kurtosis Mri Omentioning
confidence: 99%
“…In spite of the diversity in DWI protocols (e.g., the lack of standardization and the presence of artifacts), ADC estimation and interpretation methods across clinical sites [9,29], and composition of breast lesions in the studies [21,[30][31][32][33], there is common agreement that DWI is sensitive to tissue microstructure and cellularity and provides quantitative information that can be used for lesion characterization. The improved lesion characterization can reduce the number of unnecessary biopsy recommendations [6,7,34,35], which has been further validated in a multicenter trial [13]. The quantitative nature of ADC measures combined with relatively short acquisition times, typically in the order of 2-4 min but not exceeding 5 min, makes it an ideal imaging biomarker candidate [36].…”
Section: Introductionmentioning
confidence: 98%
“…Diffusion-weighted imaging (DWI) is emerging as a key imaging technique to complement dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) of the breast. DWI can be used to distinguish between benign and malignant breast lesions [1][2][3][4][5][6][7][8][9][10][11][12][13], stratify in situ from invasive disease [14][15][16][17][18], and potentially predict the response to and monitor the effect of neoadjuvant treatment over time [19][20][21][22][23][24][25]. Excellent reviews can be found in the literature; however, there is still no clear consensus within the literature on where and how breast DWI should be applied.…”
Section: Introductionmentioning
confidence: 99%